Repensando a formação continuada de professores a partir das tecnologias digitais - Menezes, Alexandre (2021)
This work addresses the importance of digital technologies for the continuing education of elementary education teachers, bearing in mind the urgent needs for adapting teaching to the remote form. Its general objective is to understand the importance of technological education in the continuing education of teachers in the early years of from the municipal public school Frei Paulo-SE, so that you can check if there was or is there any action that promotes the preparation for teaching these professionals. in relation to the use of education technologies, and suggest a workshop with the padlet device to collaborate in the pedagogical redesign with digital technologies. It is a qualitative research, using the questionnaire and the interview as data collection instruments. The research method is a case study, through which we obtained some results: we know some of the strategies in the continuing education of teachers and some pedagogical actions carried out in the midst of the pandemic. It is considered that public education has a lot to advance in the technological field and digital inclusion, as well as in teacher training.